Equity in Education: Equal Opportunities for What? - Wahlström, Ninni (Equity, Teaching Practice and the Curriculum, 2022)
In this chapter, the focus is on the concept of equity. Equity is explored both from an institutional framework of justice and from an individual perspective of actually achieved experiences and outcomes of education. The purpose of the analysis in this chapter is to develop a framework of how the understanding of equity can constitute an important concept for research on education at different levels of a school system. Drawing on Nancy Fraser's concepts of redistribution, recognition and representation; 'the principle of parity of participation'; and Amartya Sen's and Martha Nussbaum's conceptualisation of the capability approach, this chapter elaborates a framework combining curriculum theory with the concept of equity. Thus, the two general approaches of justice are more specifically discussed in relation to education and the particular dimensions of education that become important for the development of an equitable school system. The two different approaches of equity are combined in a cohesive framework based on the analytical levels of curriculum theory.